O uso de Mapas Mentais para compreender a percepção do acadêmico de medicina sobre profissionalismo médico - Socha, Gabrielli Baschung (2020)
Introduction: Medical professionalism has in its fundamental principles the primacy for the patient's well-being, the principle of patient autonomy and the principle of social justice. It also has a commitment to competence, honesty and confidentiality, to maintain appropriate relationships with patients, to improve quality and access to care, fair distribution of resources, commitment to scientific knowledge, to properly handle conflicts of interests and to maintain professional responsibilities according to the materials made by the following institutions: American Board of Internal Medicine Foundation, American College of Physicians Foundation and European Federation of Internal Medicine. Methodology: The present study was a qualitative observational study, which sought to understand the perception of medical professionalism by medical students at UNIDEP - Centro Universitário de Pato Branco. Data were collected using mind maps and an analysis of the listed textual and graphic elements was performed to describe their perceptions of medical professionalism. Principles of competency and for professional responsibilities were listed by academics. Results: Considering the definitions for the principles of professionalism, autonomy was described in ten maps and the item most cited for professional responsibilities was the commitment to professional responsibility, which was described in 17 of the 20 maps obtained. Considering the graphic elements, the most frequent ones were a draw of a stethoscope, doctor, money and books. In all maps there was something related to medical ethics, being identified as a book, a rule document and as a person with a mouth sewn / closed (associated with confidentiality). This information provides an opportunity to understand that there is an academic knowledge about medical professionalism, which at first may be empirical, but that demonstrates the possibility of displacement with the evolution of the semesters. The information obtained will support the presence of the of medical professionalism theme in the formal curriculum, as well as planning and execution activities with this focus